Users´ expectations about the practice of nurses in a Psychosocial Care Center - Débora Biffi; Cintia Nasi (Universidade Federal do Ceará, 2016)
Objective: to understand users´ expectations about the practices of nurses from a Psychosocial Care Center, Alcohol, and Other Drugs. Methods: this is a qualitative study that used the theoretical-methodological reference of phenomenological sociology. It was developed in a Psychosocial Care Center, Alcohol and other Drugs, in which 15 users were interviewed. Results: through this research, it was seen the expectations of the users about the nurses involved in their treatments, and it is possible to verify that they considered the nurses a fundamental part of the therapeutic process. Users have shown that the bonding relationship between them and the nurses is a way to strengthen and empower their involvement with the treatment. Conclusion: the users demonstrated that they have the expectation of creating a bond of trust with the nurses, considering them as professionals able to offer assistance, guidance, and contingency for fears and anxieties.